2012
DOI: 10.1186/1757-7241-20-35
|View full text |Cite
|
Sign up to set email alerts
|

Clinician awareness of tetanus-diphtheria vaccination in trauma patients: a questionnaire study

Abstract: BackgroundMost trauma patients visit the hospital via the emergency department. They are at high risk for tetanus infection because many trauma patients are wounded. Tetanus immunity in the Korean population has been revealed to be decreased in age groups over 20 years old. It is important for emergency physicians to vaccinate patients with the tetanus booster in wound management.MethodsQuestionnaires were sent to the directors of the emergency departments of resident training hospitals certified by the Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Individual adherence of these guidelines was not examined. Previous research in other countries showed that compliance to T-PEP guidelines was poor [ 15 , 23 , 24 ]. One difficulty of adhering to the T-PEP guidelines is obtaining a patient’s appropriate vaccination history [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual adherence of these guidelines was not examined. Previous research in other countries showed that compliance to T-PEP guidelines was poor [ 15 , 23 , 24 ]. One difficulty of adhering to the T-PEP guidelines is obtaining a patient’s appropriate vaccination history [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study only examined whether health care facilities had adopted guidelines as well as which guidelines had been adopted. Compliance with the guidelines at these facilities was not studied; research in other countries suggests that actual adherence to T-PEP guidelines is poor [ 15 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the US Centers for Disease Control and Prevention, tetanus vaccines have largely contributed to the reduced tetanus surveillance and morbidity since 1990 [ 1 ]. Similarly, the incidence of tetanus in South Korea has decreased since the introduction of the diphtheria and tetanus toxoid and acellular pertussis vaccine in 1982 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike that, in a study by Yoon and his colleagues, 58.8% ofhealth care professionals stated that they do not apply vaccination as they think that injured patients have immunity for tetanus. 22 All these results suggest that health care professionals need to update their information about determination of immunization status of patients with acute injuries and establishment of appropriate immunization schedule according to wound classification. In our survey, 73.7% of participants had completed their childhood vaccination schedule; childhood immunization rates of physicians and nurses were 82% and 76% respectively.These rates were found to statistically significantly higher than non-health care professionals.…”
Section: Discussionmentioning
confidence: 99%